Improving Students’ Achievement in Writing Descriptive Text Through PWIM (Picture Word Inductive Model) at SMP Negeri 3 Siborongborong (International Journal of Education and Literature, 2023)
This study attempted to improve students’ achievement in writing descriptive text through picture word inductive model at SMP Negeri 3 Siborongborong. This title got from the result of observation that the researcher found in SMP Negeri 3 Siborongborong that many students have difficulties in writing descriptive text. Some of them do not have any ideas to write, when they have come with the idea, they do not know how to write in English. They also have difficulty in using the convention of English grammar. PWIM (Picture Word Inductive Model) is a model of study that uses pictures and words to stimulate students’ thinking inductively, from the specific thinking (looking at the picture and words) to general thinking (making the picture and the words that available become a sentence then a paragaph. By applying picture word inductive model, students can enrich their vocabularies while they identify the picture. This study was conducted by using classroom action research. The subject of this research was the students in grade VII-D SMP Negeri 3 Siborongborong. There was found that the students have low achievement in writing descriptive text. The research was conducted in two cycles. There were three meetings for each cycle. Based on the scores of writing test, it was found that students’ scores kept improving in every writing test. The students’ mean score in the first writing test was (46.57) and the students’ mean score in the second writing test was (67.10). Finally, the students’ mean score in the third writing test was (93.10).